2009
DOI: 10.1002/esp.1854
|View full text |Cite
|
Sign up to set email alerts
|

Elevated sedimentation in lake records linked to agricultural activities in the Ishikari River floodplain, northern Japan

Abstract: The purpose of this study was to examine the historical change in sedimentation rates in lakes that have been impacted by river regulation and agricultural activities in the Ishikari River floodplain. We dated sediment cores using caesium-137 ( 137 Cs) dating and tephrochronology, and we estimated sediment sources from 137 Cs concentrations in the topsoil of representative land covers. We found that, between 1739 and 1963, the distance between the lake and the main river channel and whether or not the lake was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 34 publications
1
17
1
Order By: Relevance
“…However, the number and the amount of artificial oxbow lakes gradually decreased over time in the study segment. This might be caused by landfill for farmland development, sedimentation from surrounding areas, and drawdown of the groundwater level followed by channelization (Ahn et al 2009).…”
Section: Izmentioning
confidence: 99%
“…However, the number and the amount of artificial oxbow lakes gradually decreased over time in the study segment. This might be caused by landfill for farmland development, sedimentation from surrounding areas, and drawdown of the groundwater level followed by channelization (Ahn et al 2009).…”
Section: Izmentioning
confidence: 99%
“…Many freshwater organisms, such as fishes and amphibians, have adapted to such dynamic landscapes, often exhibiting high levels of species diversity and regional endemism (Tockner & Stanford, 2002;Zedler & Kercher, 2005). However, a number of wetlands have become isolated or have disappeared due to human alterations, such as levee construction associated with agricultural development and sedimentation from surrounding land-use practices (Galat et al, 1998;Ahn et al, 2009). Fragmented lotic patches are currently widespread, although artificial ditches and streams may still connect some habitat patches (Ishiyama, Akasaka & Nakamura, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Wongsa and Shimizu (2004) indicated that land use change has a significant effect on soil eroded from hill slopes, but no significant effect on flooding for the Ishikari River basin. Ahn et al (2009) concluded that sedimentation rate increased in the Ishikari River floodplain because of agricultural development on the floodplains. However, detailed accounting of sediment sources (e.g., the type of land use) and transport in the Ishikari River basin remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%